A study of morphology of the chordae tendineae of the left ventricle in human cadaveric hearts of North West Indian population - Kirandeep Kaur Aulakh; Prachi Saffar Aneja; Shavi Garg (Wolters Kluwer Medknow Publications, 2020)
The chordae tendineae form an important part of atrioventricular apparatus connecting papillary muscles to the valve leaflets. Gross morphology of the chordae tendineae of the left ventricle was studied, and any gender differences were noted. Material and methods: 30 grossly normal cadaveric fixed in 10% formalin were studied. An incision was given along left border of heart to open the left ventricle. Gross morphology of chordae tendineae were studied. Statistical analysis: In the anterior leaflet, two strut chordae were found in both males and females in all the cases. The posterior leaflet of mitral valve showed the presence of rough zone, cleft, and basal chordae. Cleft and basal chordae were seen only in the posterior leaflet of mitral valve and not in the anterior leaflet. The number of rough zone chordae was more in the posterior leaflet than other types of chordae, and they were always present. The extent of the spread of anterolateral commissural chorda was mainly to commissural 1/3 of valve leaflet. In males, the chorda spread to commissural 1/3 of leaflet in all the cases, while in females, it was so in 86.7% of cases only. Posteromedial commissural chorda was present in 96.7% of cases.